(untitled) (Comparative & International Education Series, 2022)
The number of F1 visas issued by the U.S. Department of State to international students has declined since 2015. Although international students have a strong presence in U.S. higher education, we know little about the factors responsible for recent fluctuations in enrollments. Using data from the Student and Exchange Visitor Information System, we examine whether global perceptions of Donald Trump, as captured by Google search data, impacted international student enrollments. We find that increased searches on Trump are associated with reduced international graduate student enrollments. How to cite in APA: Amuedo-Dorantes, C., Lopez, M., & Muchow, A. (2022). The Role of global perceptions on international student enrollments in U.S. educational institutions. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 47-74). STAR Scholars. [order hardcopy ]